2018
DOI: 10.1080/15548627.2018.1458173
|View full text |Cite
|
Sign up to set email alerts
|

Novel insight into circular RNA HECTD1 in astrocyte activation via autophagy by targeting MIR142-TIPARP: implications for cerebral ischemic stroke

Abstract: Circular RNAs (circRNAs) are highly expressed in the central nervous system and are involved in the regulation of physiological and pathophysiological processes. However, the potential role of circRNAs in stroke remains largely unknown. Here, using a circRNA microarray, we showed that circular RNA Hectd1 (circHectd1) levels were significantly increased in ischemic brain tissues in transient middle cerebral artery occlusion (tMCAO) mouse stroke models and further validated this finding in plasma samples from ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
250
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(254 citation statements)
references
References 74 publications
2
250
1
1
Order By: Relevance
“…In addition, no studies have reported on the efficiency of targeting circRNAs through systemic injections in stroke patients. However, previous studies that demonstrated the regulatory properties of circRNAs in stroke models (Bai et al 2018;Han et al 2018) suggest that circRNAs have potential as therapeutic targets for treatment of ischemic stroke.…”
Section: Ischemic Brain Injurymentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, no studies have reported on the efficiency of targeting circRNAs through systemic injections in stroke patients. However, previous studies that demonstrated the regulatory properties of circRNAs in stroke models (Bai et al 2018;Han et al 2018) suggest that circRNAs have potential as therapeutic targets for treatment of ischemic stroke.…”
Section: Ischemic Brain Injurymentioning
confidence: 98%
“…CircDLGAP4 over‐expression dramatically attenuated neurological deficits and decreased infarct areas in a mouse stroke model. Furthermore, this group identified circHECTD1, which was increased in the ischemic mouse brain and in the blood of individuals who had suffered a stroke (Han et al ). Knockdown of circHECTD1 expression ameliorated astrocyte activation and decreased infarct areas in mice through regulation of miR‐142 targets.…”
Section: Circrnas In Neurological Disordersmentioning
confidence: 99%
“…7,8 For example, a study discloses that knockdown of circRNA HECTD1 attenuates infract size and decreases neurological deficits in cerebral ischemia transient middle cerebral artery occlusion mouse (tMCAO) stroke models. 7 Besides that, a preliminary study based on primary cultures of alveolar macrophages from silicosis patients demonstrates that circRNA HECTD1 involves in SiO 2 -mediated inflammation cascade. 8 Based on the role of circRNA HECTD1 in enlarging stroke infarct size, accelerating neurological deficits, and inflammation from previous studies, we hypothesized that circRNA HECTD1 may be involved in the development and progression of AIS.…”
mentioning
confidence: 99%
“…In addition, central excitotoxicity enhanced neuronal autophagy, and autophagy inhibition has been proposed as a potential strategy for neuronal protection (Wang et al, ). Conversely, astrocyte autophagy restrained astrocyte activation and inflammatory cytokine production after cerebral ischemia (Han et al, ), spinal cord injury (Goldshmit et al, ), oxygen–glucose deprivation, and reoxygenation (Li et al, ). The findings from these studies suggest that autophagic mechanisms differ in different cell types.…”
Section: Introductionmentioning
confidence: 99%